Finnish botanists in the mires of Olonets region in Russian Karelia during the Second World War - Lindholm, Tapio; Heikkilä, Raimo; Kuznetsov, Oleg (International Mire Conservation Group and International Peatland Society, 2022)
In this article we compile wartime botanical information about mires in Olonets region (Russian Karelia) and compare it with new data collected as part of the Finnish-Russian cooperation in mire research. We also describe the historical background of both the local economy and the visits of Finnish botanists, which date back to the days of the Grand Duchy of Finland and the Russian Empire but were most active during the Second World War. For Finnish mire research, these excursions have allowed important comparisons between the mostly degraded rich fens of southern Finland and largely pristine examples in Olonets region. In the 2000s, 176 vascular plant and 53 moss species, corresponding to 40–50 % of the Karelian mire flora, have been recorded in this area; more than 20 different mire plant communities (associations) have been identified; and one site has been confirmed as the oldest studied mire in East Fennoscandia (12,700 years). The understanding arising from this research is especially important for nature conservation work in the Republic of Karelia.